Antibiotic stewardship in UK surgical departments: challenges and possible solutions. (2021) - Callan, Rory; Loud, Emily
Abstract : Antibiotics are one of the most widely used classes of drugs within hospitals in the UK. They have a wide range of uses within all surgical specialties, both as preoperative prophylaxis and for treatment of acute surgical conditions. Antimicrobial resistance has increasingly been seen as a major issue, as the production of new antibiotics has decreased and overall use worldwide has increased. With the COVID-19 pandemic increasing concerns about antimicrobial resistance, there is an ever-increasing need for action. This article examines the particular challenges of antibiotic stewardship in surgical departments within the UK, and outlines possible solutions for improving adherence and reducing the risk of antimicrobial resistance in the future.